The Lion of Mars - Holm, Jennifer L. (New York : Random House, 2021)
"Bell has spent his whole life - all eleven years of it - on Mars. But he's still just a regular kid - he loves cats, any kind of cake, and is curious about the secrets the adults in the US colony are keeping. Like, why don't have contact with anyone on the other Mars colonies? Why are they so isolated? When a virus breaks out and the grown-ups all fall ill, Bell and the other children are the only ones who can help. It's up to Bell - a regular kid in a very different world - to uncover the truth and save his family ... and possibly unite an entire planet."--|cPublisher's description.
Includes bibliographical references (page 257).
Keywords: Space colonies -- Juvenile fiction; Secrecy -- Juvenile fiction; Viruses -- Juvenile fiction; Self-reliance in children -- Juvenile fiction; Life change events -- Juvenile fiction; Space colonies -- Fiction; Secrets -- Fiction; Viruses -- Fiction; Self-reliance in children -- Fiction; Life change events -- Fiction; Mars (Planet) -- Juvenile fiction; Mars (Planet) -- Fiction